Remodeling the Human Adult Stem Cell Niche for Regenerative Medicine Applications - Silvana Bardelli; Marco Moccetti (Stem Cells International, 2017)
The interactions between stem cells and their surrounding microenvironment are pivotal to determine tissue homeostasis and stem cell renewal or differentiation and regeneration in vivo. Ever since they were postulated in 1978, stem cell niches have been identified and characterized in many germline and adult tissues. Comprehensive studies over the last decades helped to clarify the critical components of stem cell niches that include cellular, extracellular, biochemical, molecular, and physical regulators. This knowledge has direct impact on their inherent regenerative potential. Clinical applications demand readily available cell sources that, under controlled conditions, provide a specific therapeutic function. Thus, translational medicine aims at optimizing in vitro or in vivo the various components and complex architecture of the niche to exploit its therapeutic potential. Accordingly, the objective is to recreate the natural niche microenvironment during cell therapy process development and closely comply with the requests of regulatory authorities. In this paper, we review the most recent advances of translational medicine approaches that target the adult stem cell natural niche microenvironment for regenerative medicine applications.